Tanshinone IIA therapeutically reduces LPS-induced acute lung injury by inhibiting inflammation and apoptosis in mice - XU Min; CAO Fa-le; ZHANG Yu-fei; SHAN Liang; JIANG Xiao-ling; AN Xiao-jing; XU Wei; LIU Xiu-zhi; WANG Xiao-yan (Acta Pharmacologica Sinica, 2017)
Aim: To study the effects of tanshinone IIA (TIIA) on lipopolysaccharide (LPS)-induced acute lung injury in mice and the underlying mechanisms. Methods: Mice were injected with LPS (10 mg/kg, ip), then treated with TIIA (10 mg/kg, ip). Seven hours after LPS injection, the lungs were collected for histological study. Protein, LDH, TNF-α and IL-1β levels in bronchoalveolar lavage fluid (BALF) and myeloperoxidase (MPO) activity in lungs were measured. Cell apoptosis and Bcl-2, caspase-3, NF-κB and Hif-1α expression in lungs were assayed. Results: LPS caused marked histological changes in lungs, accompanied by significantly increased lung W/D ratio, protein content and LDH level in BALF, and Evans blue leakage. LPS markedly increased neutrophil infiltration in lungs and inflammatory cytokines in BALF. Furthermore, LPS induced cell apoptosis in lungs, as evidenced by increased TUNEL-positive cells, decreased Bcl-2 content and increased cleaved caspase-3 content. Moreover, LPS significantly increased the expression of NF-κB and Hif-1α in lungs. Treatment of LPS-injected mice with TIIA significantly alleviated these pathological changes in lungs. Conclusion: TIIA alleviates LPS-induced acute lung injury in mice by suppressing inflammatory responses and apoptosis, which is mediated via inhibition of the NF-κB and Hif-1α pathways.